Personal factors influencing the information behavior of scientists and specialists - O. L. Lavrik; M. A. Pleshakova; T. A. Kalyuzhnaya; O. A. Fedotova (Библиосфера)
The article reviews results of the surveying scientists employees of scientific centers of the Siberian Branch of the Russian Academy of Sciences - to study their information behavior. It reveals researchers’ preferences, peculiarities of their work with heterogeneous information and ways of its obtaining depending on a certain factor (status, age, area of knowledge, nature of activity, geographical location). The authors conclude on the need to renovate the information support system for research and development, and outline the strategy basic principles of developing the academic libraries scientific-information activities. The paper presents three-element model of information support for scientific research by the academic library.